All-optical logic gate computing for high-speed parallel information processing - Shuming Jiao; Junwei Liu; Liwen Zhang; Feihong Yu; Guomeng Zuo; Jingming Zhang; Fang Zhao; Weihao Lin; Liyang Shao (Opto-Electronic Science, 2022)
Optical computing and optical neural network have gained increasing attention in recent years because of their potential advantages of parallel processing at the speed of light and low power consumption by comparison with electronic computing. The optical implementation of the fundamental building blocks of a digital computer, i.e. logic gates, has been investigated extensively in the past few decades. Optical logic gate computing is an alternative approach to various analogue optical computing architectures. In this paper, the latest development of optical logic gate computing with different kinds of implementations is reviewed. Firstly, the basic concepts of analogue and digital computing with logic gates in the electronic and optical domains are introduced. And then a comprehensive summary of various optical logic gate schemes including spatial encoding of light field, semiconductor optical amplifiers (SOA), highly nonlinear fiber (HNLF), microscale and nanoscale waveguides, and photonic crystal structures is presented. To conclude, the formidable challenges in developing practical all-optical logic gates are analyzed and the prospects of the future are discussed.